Nivel de estrés en docentes de educación primaria de una escuela del Norte de Lima: Level of stress in primary school teachers in a school in the North of Lima - Yovera-Sandoval, Elizabeth Maria (2021)
Objectives: Determine the level of stress in primary school teachers. Materials and methods: Descriptive cross-sectional study. The population was made up of primary education teachers from a State Educational Institution (IE) located in the district of Carabayllo, belonging to North Lima. Stress was evaluated with the Stress Profile for Teachers. Results: A total of 34 primary school teachers participated, 91.2% (n = 31) male and the remaining fraction female. According to the length of professional service, 85.3% (n = 29) were ? 5 years old, and 67.6% (n = 23) were nominated teachers. Of the sample, 47.1% (n = 16) presented high stress level, 29.4% (n = 10) moderate stress, and 23.5% (n = 8) low stress level. In the dimension physical symptoms of stress, a significant difference (p = 0.047) was found in the mean scores between teachers who had a service time of less than 5 years compared to those with a longer professional service time, 14.80 (SD = 3 , 70) and 11.38 (SD = 3.37), respectively. Conclusions: In primary school teachers, the high level of stress is a frequent problem regardless of employment status, gender, and length of professional service. The physical symptoms of stress mainly affect teachers with less time of service. Faced with these issues, it is recommended to provide all preventive measures that lead to the reduction of stressful conditions in the educational community.